ANALISIS ASPEK PERPAJAKAN ATAS USAHA JASA KONSTRUKSI DALAM PEMENUHAN KEWAJIBAN PERPAJAKAN - Bayu Sarjono (Jurnal Bisnis Terapan, 2017)
Taxes is one of the most important sources of national income, which is taxes are a main sources in sustaining government and development in a country. Indonesia is a developing country so it is not in spite of the various infrastructure development. In view of its development, the construction sector contributed substantially as the drivers of national economic growth.This study using qualitative research with the aim to analyze aspects of the income tax and value added tax on construction industry. Aspects of taxation to the construction businesses has characteristics with other business. The method of recognition of income used is the percentage of completion method. The results of research showed that revenue from construction businesses income tax withholding has been made final income tax by the Treasurer, while the income derived from procurement of goods this failure code in the remittance of taxes, so have to make a balance transfer application. In the Value Added Tax, taxable person/entrepreneurs are overpaid VAT because the entire transaction was opposed to VAT collector.